AMMONIA INHIBITION IN THERMOPHILIC ANAEROBIC DIGESTION OF DAIRY CATTLE MANURE - Sutaryo, S.; Ward, A. J.; Moller, H. B. (Diponegoro University, 2014)
This study investigated the effect of five different concentrations of total ammonia nitrogen (TAN)and free ammonia (FA) on the methane yield and digester performance under thermophilic conditions(50°C). Five identical continuously fed digesters were used. The experiment was run for four timeshydraulic retention time (HRT). Data were statitically analysed using the data Analysis Tool Packavailable with the Microsoft Excel program. Different ammonia levels were obtained by pulsing urea toobtain the target level of TAN and FA, and to subsequently maintaining the concentration of ammonialevels by daily urea additions. The result showed a strong negative correlation between both TAN andFA concentrations and methane yield. The methane yield was reduced by 24, 30, 52 and 66% indigesters that had TAN levels of 2.9, 3.6, 4.4 and 5.1 g/L, respectively, corresponding to 0.7, 1.1,1.5 and1.8 g/L FA. Total volatile fatty acid and especially isovaleric and isobutyric acid concentrations wereelevated during ammonia inhibition. Concentration of TAN in the biogas digester exceeding 3 g/Lindicating that very often the full biogas potential is not achieved due to ammonia inhibition and thatlonger HRT should be used to compensate or a lower process temperature should be chosen.